The influence of 1Malaysia logo towards consumers in Malaysia - Nurul Ashykin Abd Aziz; Nurul Aien Abd Aziz; Noreen Noor Abd Aziz; Hasif Rafidee Hasbollah; Nur A’mirah Mohd Yaziz (Faculty of Entrepreneurship and Business,UMK, 2015)
The 1Malaysia logo has been used widely in all over the nation in various industries either in the private or in the government sectors. It is a popular logo in Malaysia that can be seen in many places. Recently, the logo received lot of attention in the business sectors. The 1Malaysia logo has been used actively by many organizations and applied it in their product packaging. This study aim to provide insights in understanding the impact of the 1Malaysia logo towards the consumers.A qualitative method were used in this research via in depth interviews towards 13 respondents. Four themes have emerged to explain the impact and the influences of 1Malaysia logo on consumer products. The theme for every question was coded by applying the thematic analysis. Data analysis was done by employing Nvivo.The findings of this study contribute to the balance theory in providing a justification on the concept of inferior, average, and superior image, whether there is a significant impact on the usage of certain images which could trigger the customers to purchase certain products. The explanation on why certain images had been used by the profit- oriented organization in their business and how do customer perceives it also will be explained. It also indicated that consumers have a negative effect on perception towards the 1Malaysia logo and it does not influence them to buy the products.